Development and implementation of scheduling and routing policies of self guided vehicles in an industrial printing application - Kappagantula Anjaneya Prasad. (2008)
The real-time representation of the SGV system and its control system design are presented. Several vehicle-initiated and workstation initiated demand selection rules as well as scheduling policies for the available jobs are proposed. Using a shortest path generation heuristic algorithm, a conflict-free traffic control can be achieved.